(untitled) (Research, Society and Development, 2021)
The management of produced water is a huge challenge for oil companies, as environmental agencies use increasingly strict laws and require a primary treatment for the disposal of waste. The conventional methods used in the treatment of oily water, cannot satisfactorily remove the environmental laws. A system is presented, with a hydrocyclone built within LABDES/UFCG, tested and characterized with oily waters with different levels of oil concentrations, in order to study its efficiency. It was observed that for different oil concentrations in the hydrocyclone feed stream of (100 to 2000) mg L-1, total oil and grease, reached an efficiency above 85%. The set of ceramic membranes, MR01-10 and MR02-20, with porosities of 43% and 52%, were used in the assembly of two types of systems, SMC-DE and SMC-FC. SMC-FC showed a removal rate above 80% for an average production of 165 L h-1 m-2. However, SMC-DE proved to be more efficient in relation to TOG, above 98%, but less efficient in relation to the permeate production flow, 63.3 L h-1.m-2. The hydrocyclone system with cross-flow ceramic membrane (SH-MC/FC) was chosen to study the reduction of oil in oily water, for a concentration range of (200 to 2000) mg L-1, which presented a removal rate above 95%.